Kedudukan dan Peran Peradilan Adat Pasca-Unifikasi Sistem Peradilan Formal - Rikardo Simarmata (Fakultas Hukum Universitas Jambi, 2021)
After the implementation of state policy on the unification of the national justice system in 1951, the customary courts are still functioning and are part of the existing customary law system. In fact, this policy abolished the position of customary court as part of the formal justice system. Customary courts continue to function after that period because the said policies did not aim to abolish the existence of customary courts, yet to negate the binding force of its decisions. Moreover, afterwards the state implemented legislation which recognizes informal forums for dispute resolution, including customary courts. The state even enacted laws and regulations whose provisions to eliminate criminal charges against someone who has been decided and given customary sanctions by the customary court. However, such legislative policies and politics do not aim to provide a strong formal position for customary courts so that they can play an important role as a dispute resolution forum favored by justice-seeking communities. This paper uses two methods to discuss the position and role of customary justice in the national justice system. The first method is by discussing two legal ideas, namely Law and Development and Access to Justice. The second method is to compare the legal politics of customary justice in two countries, namely Eritrea and Papua New Guinea. The discussion through these two methods leads this paper to a proposal regarding the need to reconsider giving binding force to customary court decisions. Abstrak Pasca-pemberlakuan kebijakan unifikasi sistem peradilan nasional pada 1951, peradilan adat tetap hidup dan menjadi bagian dari eksistensi sistem hukum adat. Padahal, kebijakan ini menghapus kedudukan peradilan adat sebagai bagian dari sistem peradilan formal. Peradilan adat tetap berfungsi setelah periode tersebut karena kebijakan unifikasi tidak bermaksud untuk mengakhiri eksistensi peradilan adat, melainkan meniadakan kekuatan mengikat dari putusannya (binding force). Apalagi, setelah itu negara memberlakukan politik legislasi yang mengakui forum-forum informal penyelesaian sengketa, termasuk peradilan adat. Bahkan, dalam perkembangannya, bermunculan peraturan perundang-undangan yang mempunyai ketentuan menghilangkan tuntutan pidana pada seseorang yang sudah diputuskan dan diberikan sanksi adat oleh peradilan adat. Kebijakan dan politik legislasi mengenai peradilan adat yang seperti itu memunculkan pertanyaan mengenai bagaimana sebenarnya kedudukan peradilan adat dalam sistem peradilan nasional. Tulisan ini menggunakan dua metode untuk mendiskusikan bagaimana kedudukan peradilan adat dalam sistem peradilan nasional. Metode pertama dengan mendiskursuskan dua pemikiran hukum yaitu Law and Development dan Access to Justice. Kedua pemikiran ini memiliki tesis-tesis yang diametral mengenai kedudukan peradilan adat. Metode kedua yaitu membandingkan dengan politik hukum terhadap peradilan adat di dua negara yaitu Eritrea dan Papua Nugini. Pembahasan lewat dua metode tersebut membawa tulisan ini pada suatu usulan mengenai perlunya mengembalikan kedudukan peradilan adat sebagai hanya forum perdamaian menjadi pengadilan yang putusannya bersifat mengikat.